البروبيوتيك تأثير البروبيوتك في الوقاية من داء الأكريات عند دجاج اللحم: Effect of Probiotics on Coccidiosis control of Broiler Chickens (Journal of Hama University, 2023)
Coccidiosis in chickens is one of the most common and widespread diseases of poultry.   Coccidiosis can lead to serious economic losses due to elevated morbidity and mortality and low feed conversion ratio as a result of inflammation and damages to the intestinal mucosa. E. acervulina is one type of Eimeria diseases in broiler chickens, which usually causes subclinical infection. While E. tenella is one of the most economically important diseases in broiler chickens which causes hemorrhage in the cecum. The experiment was designed in five groups, each group included 33 one-day-old chicks raised up to 42 days of age. It was divided into a negative control that was not infected and without any additives, a positive control group, a water probiotics group, where the probiotics were added with drinking water from the first day, and the fodder probiotics group where Probiotics were added to the feed from the first day and the salinomycin group, whereby salinomycin was added from the first day to the feed. The four groups were infected with E. acervulina and tenella together at the age of 15 days.The productive efficiency was studied after the experimental infection with E. acervulina and tenella by studying the forage conversion factor (FCR) and the European production efficiency factor (EPEF) for the experimental groups. The symptoms, anatomical characteristics, mortality, and number of oocyst in the feces of infected birds were studied. The results showed that the use of both probiotics through water Or feed and salinomycin contributed to alleviating the apparent symptoms and the degree of infection, as well as reducing the mortality rate.It was noted that there were significant significant differences (P
Keywords: Coccidiosis - Eimeria acervulina - Eimeria tenella - probiotic - broiler chickens